Advanced Mechanics of Composite Materials and Structures - Vasiliev, Valery V.; Morozov, Evgeny V. (Elsevier, 2018)
Advanced Mechanics of Composite Materials and Structures analyzes contemporary theoretical models at the micro- and macro levels of material structure. Its coverage of practical methods and approaches, experimental results, and optimization of composite material properties and structural component performance can be put to practical use by researchers and engineers. The fourth edition has been updated to reflect new manufacturing processes (such as 3D printing of two matrix composite structural elements) and new theories developed by the authors. The authors have expanded the content of advanced topic areas with new chapters on axisymmetric deformation of composite shells of revolution, composite pressure vessels, and anisogrid composite lattice structures. This revision includes enhanced sections on optimal design of laminated plates and additional examples of the finite element modelling of composite structures and numerical methods. Advanced Mechanics of Composite Materials and Structures, Fourth edition is unique in that it addresses a wide range of advanced problems in the mechanics of composite materials, such as the physical statistical aspects of fiber strength, stress diffusion in composites with damaged fibers, nonlinear elasticity, and composite pressure vessels to name a few. It also provides the foundation for traditional basic composite material mechanics, making it one of the most comprehensive references on this topic.